2018
DOI: 10.3332/ecancer.2018.805
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic validity of fine-needle capillary cytology in palpable tumours

Abstract: ObjectiveTo evaluate the diagnostic validity of fine-needle capillary cytology (FNCC) in palpable tumours.Material and methodsA retrospective, single-tray, cross-sectional diagnostic test study was carried out. We reviewed the cytological reports of the case files of the Cytology Unit of the Northern Regional Institute of Neoplastic Diseases (IREN) from January 2012 to December 2016.ResultsA total of 332 patients were selected, with an average age of 54.77 years (range 13–90 years); 61.4% of patients were fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Depending on their availability, flow cytometry, IHC, molecular analysis, genetic studies, culture, and polymerase chain reaction (PCR) for infections can all be performed on the FNAB material, and increase the diagnostic value of the FNAB. [16][17][18] The use of these ancillary tests is well established and rapidly developing in HIC, especially in the era of personalized medicine. 19 A study reported that core biopsy is superior to fine-needle aspiration (FNA) in the tissue sampling of lymph nodes regardless of ultrasound-determined risk of malignancy.…”
Section: Cytopathology Is a Screening And Diagnostic Toolmentioning
confidence: 99%
“…Depending on their availability, flow cytometry, IHC, molecular analysis, genetic studies, culture, and polymerase chain reaction (PCR) for infections can all be performed on the FNAB material, and increase the diagnostic value of the FNAB. [16][17][18] The use of these ancillary tests is well established and rapidly developing in HIC, especially in the era of personalized medicine. 19 A study reported that core biopsy is superior to fine-needle aspiration (FNA) in the tissue sampling of lymph nodes regardless of ultrasound-determined risk of malignancy.…”
Section: Cytopathology Is a Screening And Diagnostic Toolmentioning
confidence: 99%
“…Four years later, Bardales and Abad implemented FNA and FNC in the Northern Regional Institute of Neoplastic Diseases, using predominantly 27 and 25G needles. This experiment constituted the first national publication on this matter [ 7 ]. To date, interventional cytopathology has been adopted in other institutions for early diagnosis in oncology, staging, evaluation of the response to treatment and even as a screening test [ 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can also provide a definitive diagnosis, supported in the clinical context with imaging and auxiliary studies. Flow cytometry, immunocytochemistry, molecular analysis and genetic studies increase the diagnostic value of the technique [ 7 , 15 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations